2017
DOI: 10.1590/1678-4685-gmb-2016-0106
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Na+ and K+ homeostasis in plants: towards improved salt stress tolerance in crop plants

Abstract: Soil salinity is a major abiotic stress that results in considerable crop yield losses worldwide. However, some plant genotypes show a high tolerance to soil salinity, as they manage to maintain a high K+/Na+ ratio in the cytosol, in contrast to salt stress susceptible genotypes. Although, different plant genotypes show different salt tolerance mechanisms, they all rely on the regulation and function of K+ and Na+ transporters and H+ pumps, which generate the driving force for K+ and Na+ transport. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
324
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(368 citation statements)
references
References 147 publications
(361 reference statements)
5
324
0
1
Order By: Relevance
“…membrane‐localized SOS1 and the tonoplast‐localized NHX1 that mediate Na + exclusion either back into the soil or compartmentalize Na + in the vacuole, respectively (Almeida et al . ). In addition, K + transport proteins such as HKT control the long‐distance transport of Na + by reabsorbing it back into root cells from the xylem sap, thereby reducing the Na + concentration in aboveground plant parts (Rus et al .…”
Section: Discussionmentioning
confidence: 97%
“…membrane‐localized SOS1 and the tonoplast‐localized NHX1 that mediate Na + exclusion either back into the soil or compartmentalize Na + in the vacuole, respectively (Almeida et al . ). In addition, K + transport proteins such as HKT control the long‐distance transport of Na + by reabsorbing it back into root cells from the xylem sap, thereby reducing the Na + concentration in aboveground plant parts (Rus et al .…”
Section: Discussionmentioning
confidence: 97%
“…There is a general agreement that cytoplasmic high K + /Na + ratio is a good indicator of low salt damage and high salinity tolerance (Maathuis and Amtmann, 1999; Munns and Tester, 2008). The similar physicochemical characteristics between K + and Na + affect a wide range of metabolic processes, such as enzymatic reactions and protein synthesis, and maintaining the K + /Na + ratio under stress conditions is of key importance to maintain K + homeostasis (Almeida et al, 2017; Maathuis and Amtmann, 1999; Shabala and Cuin, 2008). However, it was previously reported that for halophytes and some glycophytes plants, the K + /Na + ratio is not a good parameter to assess salinity tolerance (Colmer and Voesenek, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of Na + uptake, Na + exclusion to the soil and compartmentation of Na + from cytosol to vacuoles and control of Na + loading in xylem are crucial mechanisms for salinity tolerance [39,40]. Many of these salt tolerance mechanisms depend on H + , K + and Na + transporters, such as SOS1, HKT, HAK and NHX to maintain the cellular ionic homeostasis for salt tolerance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Salinity stress reduces soil water potential, and thus, induces water deficit and rapidly transmits a water deficit signal from root to shoot and finally contributes intracellular turgor reduction [41]. Therefore, salinity results in a reduction in stomatal conductance, the most significant response that immediately occurs after plant exposure to salt.…”
Section: Discussionmentioning
confidence: 99%